Analyse multifactorielle des caractéristiques de conformation et de composition des oeufs de la dinde industrielle - Guechgal, Oussama (My University, 2020)
The study focuses on assessing the quality of a large number of industrial eggs (120 eggs) and highlighting these characteristics of external and internal quality. Through the study, the parameters were determined and This was followed by a study and statistical analysis. The results show that the coefficient of variation recorded a variability between the parameters (0.024 for the circumference of the egg and 0.14 for the height of the blank), the maximum of the parameters are significantly and strongly correlated with each other except the height white and shell thickness show a weak correlation. (r = -0.06) Estimates of the phenotypic correlations between egg parameters indicate that among the three major egg components, albumen and girth were found to have the strongest relationship with whole egg weight (+0.89; P <0.001). The total variance of the components is 53.2 based on the analysis of the principal components (Cp2).
Keywords: eggs; quality; height; correlation; variance